2010
DOI: 10.1158/1078-0432.ccr-09-2594
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the CpG Island Methylator Phenotype in Colorectal Cancer Prognosis Depends on Microsatellite Instability Screening Status

Abstract: Purpose: The aim of this study was to relate the CpG island methylator phenotype (CIMP; characterized by extensive promoter hypermethylation) to cancer-specific survival in colorectal cancer, taking into consideration relevant clinicopathologic factors, such as microsatellite instability (MSI) screening status and the BRAF V600E mutation.Experimental Design: Archival tumor samples from 190 patients from the Northern Sweden Health and Disease Study (NSHDS) and 414 patients from the Colorectal Cancer in Umeå Stu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

18
147
2
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 156 publications
(169 citation statements)
references
References 46 publications
18
147
2
2
Order By: Relevance
“…[20][21][22][23] It has been argued that CpG island methylation phenotype-positive tumors constitute a distinct subtype of colorectal cancer, and have been variously associated with different features such as BRAF mutation, KRAS mutation, favorable prognosis and adverse outcome. [24][25][26][27][28][29][30]42 These differences are likely related to different criteria used for defining CpG island methylation phenotype-positive status, as well as the number and type of markers used. The role of methylation in signet ring cell carcinoma has not been systematically explored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[20][21][22][23] It has been argued that CpG island methylation phenotype-positive tumors constitute a distinct subtype of colorectal cancer, and have been variously associated with different features such as BRAF mutation, KRAS mutation, favorable prognosis and adverse outcome. [24][25][26][27][28][29][30]42 These differences are likely related to different criteria used for defining CpG island methylation phenotype-positive status, as well as the number and type of markers used. The role of methylation in signet ring cell carcinoma has not been systematically explored.…”
Section: Discussionmentioning
confidence: 99%
“…Some, but not all, studies have shown that CpG island methylation phenotype-positive phenotype is associated with aggressive behavior. [26][27][28][29][30] BRAF is a downstream gene in the KRAS pathway. BRAF V600E mutation occurs in 34-80% of cancers with high level of microsatellite instability and 5-15% of microsatellite-stable cancers.…”
mentioning
confidence: 99%
“…Along with others, we have reported a worse prognosis in colorectal cancer patients with CIMP-low or CIMP-high, compared with CIMPnegative tumors, particularly in combination with MSS. 4,[9][10][11][12] However, results from other large studies have not been entirely consistent, [13][14][15][16][17][18] and consensus has thus not been reached. One factor contributing to the discrepancy of results in the many studies is the lack of information regarding BRAF mutation, which has shown to be a major confounding factor in studies of CIMP status and colorectal cancer patient survival.…”
mentioning
confidence: 95%
“…One factor contributing to the discrepancy of results in the many studies is the lack of information regarding BRAF mutation, which has shown to be a major confounding factor in studies of CIMP status and colorectal cancer patient survival. 12,14,15,17 Some studies have focused on the clinical importance of the host response in terms of tumor infiltrating immune cells. Presence of peri-and intratumoral inflammatory cells has consistently been associated with a better prognosis in colorectal cancer.…”
mentioning
confidence: 99%
“…Jass, 14 Jass et al 15 and Young et al 16 were the first to notify and to report the differences between these cancers. [14][15][16] Several studies have since focused on and addressed this issue, [17][18][19][20] showing that CIMP-H microsatellite-unstable colorectal cancers exhibit increased incidence rates in female patients, increased localization to the proximal large bowel, later age of onset, more frequent poor differentiation, increased frequency of BRAF mutation, increased nodal metastasis, and shortened survival time.…”
mentioning
confidence: 99%